Uji Kinerja Burner LPG Mesin Stirling dengan Variasi Tekanan Bahan Bakar - Jufrizal, Jufrizal; Mawardi, Mawardi; Ramadhan, Fandy (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
This paper is the result of initial research on the development of an LPG burner planned for the Gamma-type Stirling engine. The purpose of this study was to determine the effect of variations in fuel pressure on flame temperature and mass flow rate of fuel in LPG burners. This research method was carried out experimentally by varying the fuel inlet pressure on the regulator to the LPG burner from high to low. The LPG fuel used is 3 kg LPG produced by PT Pertamina (Persero). The pressure drop in the LPG gas tanks was varied and observed in a range of values between 20-17.5 kg/cm2, 15-12.5 kg/cm2, and 10-7.5 kg/cm2. In testing 20-17.5 kg/cm2, 15-12.5 kg/cm2, and 10-7.5 kg/cm2 the average fire temperature is 724.6°C, and 743.6°C respectively. , 631.4°C. Meanwhile, the mass flow rate of the fuel according to the order of pressure variations was 0.131 kg, 0.264 kg, and 0.162 kg respectively for 1 hour of testing. The temperature and mass flow rate of the fuel produced will be the basis for consideration in the Stirling engine design.